URETERAL TRIPLICATION AND CONTRALATERAL DUPLICATION WITH VESICOURETERAL REFLUX - Ali, Sohrab Naushad; Ali, Aymon Naushad; Ahmad, Niqad; Ali, Mian Naushad (Journal of Ayub Medical College Abbottabad, 2014)
Ureteral triplication is a rare congenital anomaly of the urinary tract. Since the first description by Warny in 1870, approximately 100 known cases have been reported in the literature, often accompanied by a variety of associated anomalies in contralateral kidney. This report presents a case of ureteral triplication with contralateral duplication and vesicoureteral reflux (VUR) of the upper moiety on the triplicate side. The patient was a 10 year old male who presented with a history of recurrent urinary tract infections and right loin pain. ACT urogram was performed which showed a triplicate right ureter with gross hydroureter of the upper moiety. There was a duplex system present on the left side. The patient underwent right upper pole heminephroureterectomy. Keywords: Hydronephrosis, vesicoureteric reflux, ureteral, duplication, triplication